A pocket drum: the groove from the perspective of pandeiro grave (Orfeu, 2024)
This article aims to investigate some of the transformations in the Brazilian pan-deiro language that occurred from the 90s onwards, especially through the work of percussionist Marcos Suzano and the ge-neration of pandeiro players who followed his legacy, referred to in this work as Pan-deiro Grave. This new pandeiro school has as one of its characteristics the expansion of the pandeiro repertoire beyond the tra-ditional styles in which this instrument is inserted, bringing the pandeiro closer to genres of American pop music such as funk and rock. This opening of the pandeiro to new styles, exotic to Brazilian music and which has the idea of groove as a funda-mental stone, makes it absorb much of the language of the drum-set, a hegemonic instrument in these genres. This made it possible to create new technical, aesthetic and technological horizons for the Brazi-lian pandeiro.
Keywords: tambourine; popular music; percussion; brazilian music